Online data collection strategies used in qualitative research of the health field: a scoping review - Pétala Tuani Candido de Oliveira Salvador; Kisna Yasmin Andrade Alves; Cláudia Cristiane Filgueira Martins Rodrigues; Lannuzya Veríssimo e Oliveira (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To identify and map the online data collection strategies used in qualitative researches in the health field. Methods: This is a scoping review guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) from the Joanna Briggs Institute. We analyzed scientific articles, theses and dissertations from 12 databases. The analysis was made by descriptive statistics. Results: The final sample consisted of 121 researches. It was found that the number of publications increased sharply in the last five years, with predominance of studies from the United Kingdom. The highlight fields were psychology (28.1%), medicine (25.6%) and nursing (12.4%). The publications used 10 online data collection strategies: Online questionnaires, online forums, Facebook, websites, blogs, e-mail, online focus group, Twitter, chats, and YouTube. Conclusions: Online data collection strategies are constantly expanding and increasingly used in the health area.